SERUM AND URINE SIALIC ACID MEASUREMENT IN CHRONIC RENAL DISEASES IN CHILDREN - NAGATA, Kishiro; KURONUMA, Tadayuki; SATO, Isamu; FUJITA, Makoto (Japanese Journal of National Medical Services, 1984)
We measured serum and urine sialic acid (SA) in 52 cases of chronic renal diseases during childhood and the following results were obtained. 1) Serum SA levels were high in the active stage of steroid sensitive nephrotic syn-drome (SSNS) and became normalized in the remission stage. Some cases in the nephrotic stage of membranoproliferative glomerulonephritis (MPGN), focal glomerular sclerosis (FGS) and chronic glomerulonephritis (CGN) showed high SA levels. Patients with per-sistent glomerulonephritis (PGN) showing high serum SA level had moderate proteinuria or frequent attacks of infection. In nephropathy associated with Wilson disease, serum SA levels were low, on the other hand in a case of hepatic glomerulosclerosis, that was high. 2) Urine SA levels were high in 3 cases of SSNS, 1 case of MPGN, 1 case of CGN, 2 cases of PGN and 1 case of Debre de Toni Fanconi Syndrome and these cases had massive or moderate proteinuria, or reduced renal functions. 3) In one case of PGN serial measurements of the SA level during fibrinolytic therapy demonstrated low SA level in the urine during the early stage of the therapy. It seems that the serial measurements of serum and urine SA levels are useful in assessing the disease condition of chronic renal diseases